Site-specific control of alloy property through binder jet 3D printing - Chiang, Po-Ju (Nanyang Technological University, 2024)
The ability to tailor the various properties of an alloy at different spatial locations (i.e. site-specifically) offers another design parameter to optimize structural parts in mechanical or chemical properties, as well as production cost. Location-based composition control using traditional manufacturing processes is very difficult since they are usually focused on shaping and any differences in composition and properties at different locations in the part are usually a side product of the process. Additive manufacturing (AM) provides the unique opportunity to tune materials at any location within the print volume by adjusting the processing parameters, so that dissimilar microstructures can be integrated within the builds to impart multiple properties. A variety of site-specific microstructures has already been demonstrated using fusion-based AM technologies, which allows for control over grain size, crystallographic orientation, grain-boundary characteristics, and phase formation. In contrast, little work has been carried out on other AM processes, such as the binder jet 3D printing (BJ3DP). The advantage of BJ3DP over other AM modalities is that printing can be performed rapidly at high resolution without producing residual stress in any significant amounts. The binder is also compatible with a lot more materials than lasers and electron beams, including high-reflective metals and ceramics. In addition, by adjusting the type of binders deposited, BJ3DP has the potential to adjust the chemical composition of alloys to directly change the resultant properties of the printed part. In this report, the effect of binder on the powder to form different microstructures after sintering was first investigated in cylindrical crucibles. The diffusion of alloying elements was observed and mitigated by designed sintering strategy and inclusion of diffusion barriers. Next, based on the learnings from trials in cylindrical crucibles with loose powder, site-specific property control was verified via BJ3DP testbeds. To prove the concept, heterogeneous parts with site-specific properties were fabricated to demonstrate the shift in fracture location away from stress-concentration geometry. Lastly, the combination of BJ3DP with spark plasma sintering was experimented, resulting in enhanced mechanical performance, and improved spatial resolution of site-specific control. In conclusion, this study demonstrates the realization of site-specific property control through tuning of local composition by BJ3DP, while addressing the challenge of part homogenization with designed sintering strategies, diffusion barrier concept, and spark plasma sintering. The results showcase new opportunities to design and produce multi-functional metal alloys and expand the knowledge base of BJ3DP.